Mengelola Kecemasan pada Masa New Normal melalui Konseling Direktif - Adiwinata, Choirun Nisa (Institut Agama Islam Negeri Parepare, 2022)
Anxiety is a form of response that arises to a threatening situation which is normally experienced by every individual. In facing the current new normal era, there are various kinds of reactions/responses from society. There are people who welcome it with joy because they can return to their activities, but there are also people who are worried. Therefore, the role of the counselor is really needed to guide people so that they are not too anxious in facing the new normal period, one of which is by means of directive counseling where the counselor dominates the counseling process to help the counselee. This research aims to find out how to manage anxiety in facing the new normal era through directive counseling. The method used in this research is descriptive qualitative with literature studies in previous research. The research results show that the implementation of the new normal causes anxiety for most people. Directive counseling is here to deal with these problems by offering five techniques, namely desensitization, assertive thinking, covert sensitization, modeling or imitation, and thought stopping. So that with directive counseling, people are able to manage anxiety and adapt to the new normal